CLINICAL EFFICACY OF JALAUKAVACHARANA ON UTTANA VATARAKTA: A CASE STUDY - Prerna R. Masatkar (AYUSHDHARA, 2021)
As described in Ayurveda there is simultaneous vitiation of Vata and Rakta along with Rasa, Rakta, Mamsa, Meda and Asthi Dhatu dushti in Vatarakta vyadhi. Vatarakta is correlated with gout in modern medical sciences. Gout is the true crystal deposition disease characterized by pain and swelling of 1st metatarso phalengial joint initially followed by other joints with an abnormal elevation of urate levels in the body either due to overproduction or under secretion or both. Chikitsa of Vatarakta includes Shaman (internal medicines), Virechana (purgation), Basti (enema), and Raktamokshana (bloodletting) as per Ayurvedic texts. Main clinical findings: In this study pt with acute gouty arthritis was correlated with Uttana Vatarakta, with symptoms like swollen lt. great toe, hot, red shiny, and extremely painful small joint. Diagnosis: As per Samprapti of Uttana vatarakta, Mrudu and Drava Guna of Pitta Dosha are vitiated to form Mrudu Shopha over the big toe. So as symptoms presented in this case study. Intervention: According to Sushrutacharya Jalaukavacharan is applicable to Mrudu Shopha. So, in the present study Jalaukavacharan was done on Shopha along with shaman Aushadhis like Kaishore Guggulu, Guduchyadi Kashaya, Kokilaksha Kwatha given internally to the patient. Outcome and conclusion: It has been observed that above treatment relieved the symptoms like localised Shopha, Raktavaivarnya, Shool and Daha.